20 Years of reconfigurable field-effect transistors: From concepts to future applications. (December 2021) - Mikolajick, T.; Galderisi, G.; Simon, M.; Rai, S.; Kumar, A.; Heinzig, A.; Weber, W.M.; Trommer, J.
Highlights: The basic concepts of reconfigurable field effect transistors (RFETs) have been demonstrated 20 years ago. Two basic device concepts have been realized in different variants in the early years of RFET development. In the last 20 years the concept of RFETs was developed toward circuit applicability and additional device features. Promising RFET applications like hardware security are currently in the development phase. Abstract: The reconfigurable field-effect transistor (RFET), is an electronic device whose conduction mechanism can be reversibly reconfigured between n-type and p-type operation modes. To enable this functionality, those devices do not rely on chemical doping caused by impurities but rather on electrostatic doping, i.e. the generation of mobile carriers via an external potential. This functionality has been first concieved in the early 2000s to reduce the source-drain leakage in ambipolar thin film transistors. Over the years many different concepts have been developed employing different conduction mechanisms as well as channel materials, such as silicon nanowires, carbon nanotubes or two-dimensional layered materials. In addition the focus the research shifted more and more towards the circuit level, bringing the unique device characteristics to fruitation. In this work, we will give an historic overview of the main development phases including thier key-achievements starting from the earlier years reaching untill today. Further, we discuss the most interesting circuit properties arising from the device functionality and summarize the broad range of their potential future applications.